Evaluasi Penggunaan Klorokuin Atau Oseltamivir Terhadap Fungsi Ginjal Pasien COVID- 19 di RSUP Fatmawati Jakarta Tahun 2020 - Juwita, Agnes (RSUP Fatmawati, 2023)
Coronavirus Disease2019 (COVID-19) is a new type of coronavirus (SARSCoV-2) that resembles a case of pneumonia. This virus was first discovered in Wuhan, China. In the early period of COVID-19 in March 2020 there was a significant increase in active cases and death cases in Indonesia. There is no therapeutic treatment for COVID-19, so the use of chlorouin or oseltamivir and other drugs being tested has the potential for COVID-19. The use of drugs outside of indications can cause a decrease in function in several organs of the body, especially in the kidneys because many drugs are excreted through the kidneys. The purpose of the study was to evaluate the suitability of therapy using chloroquine or oseltamivir with the standard COVID-19 Treatment Protocol and its effect on kidney function of COVID-19 patients at the inpatient installation of Fatmawati Hospital for the period March-June 2020. The research method was descriptive observational through tracing the medical records of COVID-19 patients. with the study subjects being inpatients with confirmed COVID-19 aged 18 years who received chloroquine or oseltamivir and had normal kidney function at Fatmawati Hospital. The effect of the use of chloroquine or oseltamivir using a pre and post design which will be analyzed using a paired t test to see levels before and after use on kidney function parameters. (57 patients) standard. A total of 49.56% (56 patients) who were not suitable for therapy included a mismatch of dosage and duration of administration. The results of the Wilcoxon Test analysis on the concomitant use of chloroquine or oseltamivir serum urea and creatinine levels had Asymp values. Sig. (2-tailed) < 0.05 means that the use of chloroquine or oseltamivir affects the patient's kidney function.